Dictatorship - Uhl, Xina M.; Brezina, Corona (Examining political systems., 2020)
Presents an overview of a dictatorship explaining its principles, structures, and history throughout the world. Includes photographs and illustrations, a timeline, primary source transcriptions, sources for further information, a bibliography, and in index.